Działania środowisk naukowych na rzecz jakości kształcenia w szkołach wyższych w dwudziestoleciu międzywojennym, na łamach czasopisma „Szkoły Akademickie” - Kula , Ewa; Pękowska, Marzena (Studia Edukacyjne, 2019)
After Poland’s regaining independence, a significant role in the organization of higher education institutions, the development of academic instruction and research as well as in the formation of awareness of the Polish academic community, was played by periodicals addressed to this group. One of such magazines was Szkoły Akademickie quarterly (1927-1928) and afterwards a yearbook (1928-1930). The article presents the questions of higher education addressed by this journal and the activities undertaken by the scientific community to solve them. The information included in the journal allowed moreover to indicate the most crucial activities of academic circles for the improvement of academic didactics and the development of scientific research.